2023
DOI: 10.3390/nu15010242
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Picky Eaters among Typically Developed Children—A Scoping Review

Abstract: Picky eating in children is often a major source of concern for many parents and caregivers. Picky eaters (PEs) consume limited foods, demonstrate food aversion, and have a limited food repertoire, which hinders their growth and health. These behaviours are common in children with special health care needs despite the rise in typically developing children. This leads to less attention being given to intervention programmes for typically developing children. Therefore, this scoping review aims to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Because BMI is not different from the other groups, their obesity may instead be related to simple overconsumption of calorie dense foods and interventions focused on increasing acceptance of healthier food items may be most beneficial. 36 The post-hoc secondary analysis to explore demographic differences in group membership indicated that group membership did not differ by patients' age. However, the Hedonic Impulsive group had fewer who were eligible for free or reduced lunch and more parents with some college education.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because BMI is not different from the other groups, their obesity may instead be related to simple overconsumption of calorie dense foods and interventions focused on increasing acceptance of healthier food items may be most beneficial. 36 The post-hoc secondary analysis to explore demographic differences in group membership indicated that group membership did not differ by patients' age. However, the Hedonic Impulsive group had fewer who were eligible for free or reduced lunch and more parents with some college education.…”
Section: Discussionmentioning
confidence: 98%
“…One could speculate that this rarest group of children probably do not like fruits or vegetables and do not have mental health or behavioural issues. Because BMI is not different from the other groups, their obesity may instead be related to simple overconsumption of calorie dense foods and interventions focused on increasing acceptance of healthier food items may be most beneficial 36 …”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the shared environment was only found to impact individual differences in fussy eating behaviour in toddlerhood, indicating environmental or family-based interventions targeting children's fussy eating behaviours (such as repeated exposure and increasing the variety of fruits and vegetables offered in the home), may be most effective in the very early years (Kamarudin et al, 2023). These findings do not imply that food fussiness cannot be changed in response to behavioural interventions; however, they suggest that it may be a more challenging behaviour to modify, especially beyond toddlerhood, in comparison to behaviours that are under predominantly environmental influence.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently no universally agreed-upon medical definition of picky eating, resulting in varying definitions across the literature [5]. This has led to a wide range of reported prevalence rates of picky eating in pediatrics across different countries, ranging from 6.4% to 54% [6][7][8]. While several studies have examined the prevalence of picky eating in childhood, few have investigated its impact on body composition and development [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have assessed the body composition of picky eaters using body impedance analysis (BIA), which is a non-invasive and quick method for measuring body composition and is thus more applicable to large-scale studies [ 13 ]. According to our literature search, this study is the first of its kind in Saudi Arabia and globally to use BIA to evaluate body composition among pediatric picky eaters, unlike the conventional methods of measuring weight, height, and x-ray absorptiometry [ 7 , 8 ]. This study aimed to assess the prevalence of picky eaters aged between three and 12 years old using BIA to identify their body composition characteristics in a tertiary care center in Riyadh.…”
Section: Introductionmentioning
confidence: 99%